2019
DOI: 10.1111/nph.16246
|View full text |Cite
|
Sign up to set email alerts
|

Lack of FIBRILLIN6 in Arabidopsis thaliana affects light acclimation and sulfate metabolism

Abstract: Arabidopsis thaliana contains 13 fibrillins (FBNs), which are all localized to chloroplasts. FBN1 and FBN2 are involved in photoprotection of photosystem II, and FBN4 and FBN5 are thought to be involved in plastoquinone transport and biosynthesis, respectively. The functions of the other FBNs remain largely unknown.To gain insight into the function of FBN6, we performed coexpression and Western analyses, conducted fluorescence and transmission electron microscopy, stained reactive oxygen species (ROS), measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 87 publications
(201 reference statements)
2
16
0
Order By: Relevance
“…The techniques employed to accomplish our goals include the mining of public databases in order to identify co‐regulated factors (guilt‐by‐association approaches), genetic screens, environmental perturbation experiments combined with ‘omics’ technologies (transcriptomics, proteomics and metabolomics) and the analysis of molecular and gene regulatory networks. For example, FIBRILLIN6 (FBN6) (Table 2) was identified as a factor involved in high light acclimation and cadmium tolerance via a guilt‐by‐association approach (Lee et al ., 2020). Moreover, a screen for mutants that can cope better than WT with lincomycin, an inhibitor of organellar translation, revealed that a disturbance in the secondary cell wall promotes early chloroplast development (Xu et al ., 2020a).…”
Section: Ra3 Signalling: Coordination Of Different Acclimation Respomentioning
confidence: 99%
“…The techniques employed to accomplish our goals include the mining of public databases in order to identify co‐regulated factors (guilt‐by‐association approaches), genetic screens, environmental perturbation experiments combined with ‘omics’ technologies (transcriptomics, proteomics and metabolomics) and the analysis of molecular and gene regulatory networks. For example, FIBRILLIN6 (FBN6) (Table 2) was identified as a factor involved in high light acclimation and cadmium tolerance via a guilt‐by‐association approach (Lee et al ., 2020). Moreover, a screen for mutants that can cope better than WT with lincomycin, an inhibitor of organellar translation, revealed that a disturbance in the secondary cell wall promotes early chloroplast development (Xu et al ., 2020a).…”
Section: Ra3 Signalling: Coordination Of Different Acclimation Respomentioning
confidence: 99%
“…The Web MicroRNA Designer program (http://wmd3.weigelworld.org/) was applied in order to generate two amiRNA constructs (amiR1 and amiR2) targeting different regions of the MTERF2 (AT2G21710) gene. The amiR constructs were generated, as described [30], while using the primers provided in Supplementary Table S1. The individual T1 seeds were selected by GFP fluorescence, and independent T3 and T4 transgenic lines were used for phenotypic analysis.…”
Section: Generation Of Amirna-mediated Knockdown Lines Gus and C-mycmentioning
confidence: 99%
“…The RNAi of LeChrC ( FBN1 ) and mutants of fbi4 in apple ( Malus domestica ) and Arabidopsis were more sensitive to Botrytis cinerea, Erwinia amylovora and Pseudomonas syringae , respectively ( Leitner-Dagan et al, 2006 ; Singh et al, 2010 ). The fbn6 mutant of Arabidopsis showed resistance to cadmium and high-light stresses ( Lee et al, 2020 ). The expression of jasmonic acid (JA) synthesis related genes in fbn5 mutants were inhibited under high-light stress ( Otsubo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%